2002
DOI: 10.1006/viro.2002.1494
|View full text |Cite
|
Sign up to set email alerts
|

Quasispecies Heterogeneity and Constraints on the Evolution of the 5′ Noncoding Region of Hepatitis C Virus (HCV): Relationship with HCV Resistance to Interferon-α Therapy

Abstract: Hepatitis C virus (HCV) polyprotein translation depends on direct internal entry of the 40S ribosomal subunit mediated by an internal ribosome entry segment (IRES) located in the 5' noncoding (5'NC) region of the viral genome. HCV is genetically heterogeneous and is characterized by the existence of a quasispecies distribution of the virus population within a single infected individual. Cloning and sequencing strategies were used to characterize 5'NC quasispecies genetically. Similar to coding regions, the HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 51 publications
4
44
0
1
Order By: Relevance
“…5' UTR ve IRES bölgesinin mutasyonlarının tedavi yanıtını etkilemesi konusunda literatürde çelişkili sonuçlar mevcuttur. Bazı çalışmalarda 5'UTR bölgesinin mutasyonlarının tedavi cevabını olumlu etkilediği belirtilirken (20,21), bazılarında ise bu bölgede görülen mutasyonlarla tedavi arasın-da bir ilişki saptanmamıştır (22,23).…”
Section: Gereç Ve Yöntemunclassified
“…5' UTR ve IRES bölgesinin mutasyonlarının tedavi yanıtını etkilemesi konusunda literatürde çelişkili sonuçlar mevcuttur. Bazı çalışmalarda 5'UTR bölgesinin mutasyonlarının tedavi cevabını olumlu etkilediği belirtilirken (20,21), bazılarında ise bu bölgede görülen mutasyonlarla tedavi arasın-da bir ilişki saptanmamıştır (22,23).…”
Section: Gereç Ve Yöntemunclassified
“…Amongst them, it is known that the high rate of virus mutations leads to the generation of a mixture of closely related genomes, the quasispecies, which persist and evolved in the infected patients (Pawlotsky., 2003a;Pawlotsky., 2003c;Rumin et al, 1999;Soler et al, 2002;von Wagner et al, 2003;Vuillermoz et al, 2004). Similar to coding regions, the 5'Non Coding Region (5'NCR) is distributed as a quasispecies. Previous studies have shown that this part of HCV genome might accumulate nucleotide substitutions, (Vizmanos et al, 1998) but it appears to be subjected strong conservatory constraints than the other regions of the HCV genome.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the need for structural conservation of the mediated translational element: the Internal Ribosome Entry Site (IRES) located in the 5'NC region. This segment (nt 40-372), highly conserved between 3 isolates (Soler et al, 2002), has the potential to form a stable secondary and tertiary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the translation of eukaryotic mRNA starting from the 5 0 -cap structure, the translation of HCV RNA initiates at the internal ribosome entry site (IRES), which encompasses most of the 5 0 -untranslated region (5 0 -UTR) and about 40 nt of the core protein-coding region (3,4). The HCV IRES is highly conserved among HCV isolates in both the primary sequence and secondary structure (5)(6)(7). Since the translation is an essential step in the viral replication and possibly in the pathogenic functions, it would be important to evaluate the activity of HCV IRES for such studies.…”
mentioning
confidence: 99%